Draft genome sequence of a novel culturable marine chroococcalean cyanobacterium from the South Atlantic Ocean - Rigonato, Janaina; Alvarenga, Danillo O.; Branco, Luis H.Z. [UNESP]; Varani, Alessandro M. [UNESP]; Brandini, Frederico P.; Fiore, Marli F. (American Society for Microbiology, 2016)
The novel chroococcalean cyanobacterium strain CENA595 was isolated from the deep chlorophyll maximum layer of the continental shelf of the South Atlantic Ocean. Here, we report the draft genome sequence for this strain, consisting of 60 contigs containing a total of 5,265,703 bp and 3,276 putative protein-coding genes.